Analysis of the lots of the Belonidae family present in the department of icthyology of the natural history museum, Universidad Nacional Mayor de San Marcos, Lima, Perú - Macedo-Bedoya, Jehoshua (2024)
The present study compiles data from 292 lots, of which 4 lots with 45 specimens belong to Belonion dibranchodon (Collette, 1966), 190 lots with 324 specimens to Pseudotylosurus angusticeps (Günther, 1866), 53 lots with 124 specimens to Potamorrhaphis eigenmanni (Ribeiro, 1915), and for Potamorrhaphis guianensis (Jardine, 1843), 40 lots with 108 specimens were recorded. The identification of taxa was corroborated after compiling taxonomic keys. Subsequently, the standard length of specimens was measured, and distribution maps were generated using DIVA-GIS. The results showed significant diversity in the Peruvian Amazon, with B. dibranchodon present in the Putumayo basin in Loreto, Potamorrhaphis distributed in Loreto, Ucayali, and Madre de Dios, and P. angusticeps with a wide distribution in several basins. The absence of Pseudotylosurus microps in the collection suggests the need for further research. The importance of continuing to explore and conserve the ichthyofauna in the Peruvian Amazon is highlighted to improve our understanding of its biological diversity and develop effective conservation strategies.